Pengaruh Pemanfaatan Azotobacter chroococcum dalam Limbah Nanas sebagai Inoculant terhadap Waktu Terjadinya Kompos Sampah Organik - Hastomo Hastomo; Sri puj Ganefati; Sri Muryani (Sanitasi: Jurnal Kesehatan Lingkungan, 2010)
Some problems raised from the existence of organic wastes should be solved properly. The problems are included potential impact to environment, leachate yielded from decomposition process, bad odour and the possiblity of becoming the breeding places for disease vectors. Composting is one of the methods that can be applied. However, in the application it needs other organic compound to shortener the time needed. In this experimental study which was employing post- test-only-with-control-group-design, inocullant from pineapple wastes and Azo- tobacter chroococcum as activator was used. The wastes were collected from Sentul Market of Yogyakarta, and the isolate of the bacteria was obtained from the Laboratory of Soil Microbiology of Faculty of Agriculture of Gadjah Mada University. Three variations, i.e. 100, 120 and 140 gr inocullant per kilogram organic waste was used. Meanwhile, the final compost was determined if the following criterias has been reached: stable room temperature, brownish black in color, neutral pH, final volume is a third from the initial one and odourless. By using one-way anova test, it can be concluded that the 140 gr inocullant poured into a kilogram of organic waste produced the shortest composting time, i.e. 23 days.